Chapter 2 Advancing Afrikan Sustainable Design - Campbell, Angus Donald (Taylor & Francis, 2024)
sustainable development,design for sustainability,Ubuntu,relations,connectedness,decolonisation,Sustainable Product Design,Energy Systems,PSS,Ivan Brown,Urban Farmers,Cradle Products Innovation Institute,Sustainable Design,Honey Badgers,Industrial Design,Decolonial Lens,Product Service System Design,Sustainable PSS,Department Of Energy,Distributed Energy Systems,Honey Bee Network,Average Monthly Household Income,Design Education,Lightweight Concrete,Post-war,Human Centred Design Approach,SDGs,Socio-technical Systems Design,Designer's Involvement,Global North,Service Differentiation Strategy